Perbandingan Penyembuhan Luka Bakar Derajat II Tikus Wistar yang Mendapatkan Lisat Platelet rich Plasma dan Putih Telur - , Pungky Prasetyo, Dr. dr. Yohanes Widodo Wirohadidjojo,Sp.KK(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : World Health Organization (WHO) report shows the mortality index of burns is about 300,000 per year. Burn on skin will cause tissue damage that lead to disruption of supply of nutrients and oxygen, and also regulation of body fluids and temperature. These conditions will delay the healing process of the burn wound. The use of growth factors that induce faster re-epithelialization and re-vascularization will shorten the duration of burn healing. Platelet-rich plasma (PRP) and platelet-rich fibrin (PRF) are the source of growth factors, which can be made from a patient's own blood. Egg is easy to get and has long been used for healing burns. Egg-whites contain a lipid that has the ability like growth factor. Objective : Determine the effect of PRF lysate and egg-whites to the second-degree burn wound healing in rat through observation of re-epithelialization (clinically and histologically) and hair regrowth. Method : Three second degree burn wounds were produced and the rats were divided into three groups according to treatment including PRF lysate, egg-white, and control. The decrease of wound areas were measured from photograph taken everyday. The epithelialization were also measured from the histological slides taken by biopsy on day 7, 14, and 21. The hair regrowth areas were measured from the diffrence between wound areas on the first and last day of the research. One-way ANOVA and Friedman statistical analysis were used to find the difference between groups with a significant value of p<0.05. Result : There is no significant differences on re-epithelialization, either clinically or histologically, between control, PRF lysate, and egg-white group (p>0.05). Subjects with complete re-epithelialization on day 14 were highest on PRF lysate group. There is a significant difference on hair regrowth between PRF lysate group vs egg-white and control. Conclusion : PRF lysate is superior than egg-white for the second degree burn wound healing in rat